The Development and Teachers’ Perception on Electromagnet Teaching Aid: Magnobolt (Jurnal Pendidikan IPA Indonesia, 2018)
Magnobolt is a teaching aid built on hands-on activity and exercises. This study examined a framework that could integrate both theoretical and practical of learning science in Malaysia. ADDIE model was used for Magnobolt module development. The perception of 300 science teachers across the Perak on Magnobolt studied via questionnaire includes two parts; Pedagogical Approach to Teaching and Learning and training suitability. The reliability for Magnobolt was tested on a total of 30 teachers which were not involved in the actual study. An analysis of the Cronbach’s Alpha exhibits 0.945 showed very good reliability. Three content domain experts were involved to evaluate the validity of the Magnobolt. A real case study on 300 science teachers agreed that the Magnobolt was developed for a pedagogical approach to teaching and learning and suitable for training with the total mean score of 4.34 and 4.25 respectively. This science module also injects the element of creativity and innovation to build fun in learning science and creative capacity of teachers.